Agreement between methods and terminology used to assess the kinematics of the Nordic hamstring exercise. Issue 24 (17th December 2021) - Sconce, Emma; Heller, Ben; Maden-Wilkinson, Tom; Hamilton, Nick
ABSTRACT: The Nordic hamstring exercise (NHE) is employed as a component of preventative training programmes to minimise hamstring strain injury risk. Variation in the methods and terminology used to assess the NHE makes comparison between studies difficult. We aimed to compare the utility of kinetic and kinematic metrics by comparing several collected concurrently. 18 male recreational rugby union participants completed 3 bilateral NHE repetitions on a hamstring device equipped with in-line strain gauge load cells, integrated with a 3-dimensional motion tracking system. Mean break-point angle occurred after the angle at first acceleration (121.5 ± 10.4° vs. 119.2 ± 7.1°) whereas break-torque angle (BTA) occurred later in the NHE action (126.0 ± 9.8°) showing highest correlation to the angle at greatest acceleration (123.9 ± 7.9°, r = 0.85). Future research should consider movement quality as the angular velocity of the knee joint at BTA demonstrated large variation ( range = 3.6–93.4 deg·s 1 ), with high intrasubject variability of relative trunk-to-thigh angle at peak-torque ( range = 0.4–44.7°). This study proposes standardisation of methods and terminology used to define the NHE. Measuring BTA is recommended to represent the point at which hamstring muscle failure occurs, specific to the proposed injury mechanism during high-speed running.